Platinum Hour: Emergency Department Length of Stay and Trauma Patients’ Outcomes - LaRosa, Samantha; Moore, Katherine; Harshaw, Nate; Voigt, Mickel; Tilvawala, Megha; Perea, Lindsey L. (The Journal of surgical research, 2024)
Trauma bay and emergency department (ED) length of stay (LOS) are important time measures in patient care. The data on this subject are inconclusive or specific to one condition. Our goal was to determine the relationship between ED LOS and outcomes or mortality of trauma patients. We sought to investigate certain cofactors which influence this relationship. We hypothesized that ED LOS will be correlated with negative patient outcomes and mortality for moderately and severely injured trauma patients. A retrospective study was conducted from June 2018 to June 2022 at our level 1 Trauma center. Patients ≥18 y that arrived as a trauma activation were included. Patients were excluded if they were transfers in or out, expired before arrival, or were discharged from the ED. Univariate and multivariable statistical analysis based on disposition time were performed. The primary outcome was mortality. Six thousand seven hundred eighty-one patients met the inclusion criteria. Patients were stratified based on time to disposition ≤60 (n = 521) and >60 min (n = 6260). The ≤60-min group was younger than the >60-min group (53 (interquartile range (IQR) 30-73) versus 68 (IQR 48-82), P < 0.001), and was more often male (69.48% (n = 362) versus 50.32% (n = 3150), P < 0.001). The ≤60-min group had a lower Glasgow Coma Scale (14 (IQR 8-15) versus 15 (IQR 15-15), P < 0.001), a longer intensive care unit LOS (2 (IQR 1-5) versus 1 (IQR 1-3), P < 0.001), a longer hospital LOS (4 (IQR 1-10) versus 3 (IQR 2-6), P < 0.001), and a greater Injury Severity Score (13 (IQR 5-22) versus 5 (IQR 4-10), P < 0.001) compared to the >60-min group. The ≤60-min group was also more likely to receive blood products (39.92% (n = 208) versus 13.15% (n = 823), P < 0.001) compared to the >60-min group. A greater risk of mortality was found in the ≤60-min versus >60-min group (17.47% (n = 91) versus 2.75% (172), P < 0.001). The ≤60-min group had a shorter transport time (14 (IQR 8-21) versus 17 (IQR 11-24), P < 0.001). On multivariable analysis, there was an association between a disposition time of 60 min or less and a decreased risk of mortality. However, men had a greater risk of mortality compared to women. Patients that received blood products and patients with more severe injuries had a higher likelihood of mortality. Trauma patients with a decreased ED LOS had a higher rate of mortality, contrary to our hypothesis. The patients with a decreased ED LOS were also more severely injured. It may be reasonable that trauma patients can receive the same level of care regardless of location in the hospital.